The induction motor - Matthews, Howard David; Dial, Thomas E. (My University, 1904)
Introduction:The induction motor is a type of alternating current motor in which the magnetic flux is furnished by either a single phase or a polyphase current. Consider the action of a compass suspended over a magnetic field, the needle thus suspended will take a position parallell to the lines of force, which flow from pole to pole. Now if the nagnet be rotated the needle will change position relative to it. If the magnet be substituted for a four pole electro-magnet as shown in Fig. 1 Plate 1 and a current of electricity be allowed to flow about either of the sets of poles, and the needle be allowed to swing freely in the center, it will set its self parallel to the lines if a current is flowing in all four poles at the same time this needle will set itself diagonally half way between the sets of poles, as illustrated by Fig. 2. Plate 1. It is now easily conceivable that, if one of these currents, in the windings of the poles is becoming weaker as the other is growing stronger, t the needle will be attracted to the former until the flux reaches its maximum value. Where an alternating current is used this process of rapidly changing from maximum to minimum tends to rotate the needle. If,now, a cylinder consisting of copper conductors be used, instead of a needle, the machine becomes an Induction Motor. The direction of rotation is determined by the phase relation of the currents, The direction of rotation may be reversed by interchanging and two wires of a three phase three wire circuit. Thus by means of polyphase currents it is very easy to produce rotating fields.
Citation: Matthews, Howard David and Dial, Thomas E. The induction motor. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Induction Motor; Mechanics; Motor Composition; Theses